The implementation of school character education program: a case study of muslim students of SMAN 12 South Tangerang - Septyana Atik Purwandari; Didin Nuruddin Hidayat (STABN RADEN WIJAYA WONOGIRI, 2022)
In today's life, some schools and parents developed and made efforts to foster and strengthen the student' character in various ways. This research aims to describe the implementation of the school character education program at SMAN 12 South Tangerang. The stages of the research are the orientation of the school program, socialization, the application, monitoring, and evaluation in the implementation. This research used a qualitative approach and descriptive method by case study. The sampling techniques were in-depth interviews, participative observation, and documentation. The data came from reports and documents from the school program coordinator, the headmaster, the teachers, and the students. The result shows that the orientation in this program is based on the school's vision and mission. Its socialization was managed by the program coordinator, the teachers, and the headmaster. Further, the application of this program is by giving semi-comprehensive approach, such as integrated subject (BTQ), extracurricular program, and reciting Quran after the school ended; monitoring and evaluation in the school character program are participation management system recorded by the academic report, the student’s attendance. There are benefits and challenges in applying to this program.